HIV/AIDS and labor markets in Tanzania - Arndt, Channing; Wobst, Peter (International Food Policy Research Institute, 2002)
We analyze the implications of the HIV/AIDS pandemic in Tanzania for labor markets and human capital accumulation. Three analyses are undertaken. First, we examine the 2000/01 Labor Force Survey and compare it with the 1990/91 Labor Force Survey. Since these two surveys encompass a period where accumulated AIDS deaths increased dramatically, their comparison provides an opportunity to make inferences about the impact of HIV/AIDS over that period. Second, we study rates of human capital accumulation, proxied by educational attainment, for the period 1991 to 2000. While the most obvious impact of HIV/AIDS on human capital comes about through the deaths of skilled people, this might not be the greatest concern in terms of long run economic impact. In poor countries with low levels of human capital, implications for rates of human capital accumulation might be of greater concern. We estimate education transition matrices to assess human capital accumulation over the 1990s and assess the trends in transition probabilities and regional variations in these trends. Finally, we analyze the implications of skills upgrading using a computable general equilibrium (CGE) model of Tanzania. We find that the age structure of the labor force is changing with 10-14 year olds and juveniles comprising a significantly larger share and prime age adults aged 20-35 a smaller share compared with 1990/91. The growth in the child and juvenile labor force is matched by a trend towards an increased tendency to exit primary school and an overall lower share of children aged 5-14 enrolled in primary school. We conclude that workforce experience and rates of human capital accumulation are declining with HIV/AIDS being a prime factor underlying these trends. The CGE analysis indicates that skills upgrading of the population has particularly large first order (segmented rural and urban labor markets) impacts on the agricultural sector since the large majority of the population is rural. If migration is permitted, the enhanced productivity of a more skilled rural labor force permits substantial growth in agricultural and non-agricultural output generating a development pattern similar to those advocated by Mellor (1976) and Adelman et al. (1989). Reduced rates of skills upgrading would slow these trends. -- Authors' Abstract.